2020
DOI: 10.3390/app11010199
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Factors That Drive to BIM Effectiveness: Technological Learning, Collaborative Culture, and Senior Management Support

Abstract: Senior management support is a key dynamic capacity for design companies in the architecture, engineering, and construction (AEC) industry, given the fact that they must identify changes in the competitive environment, which are increasingly becoming more and more technological. In addition, senior management support is obliged to react in the most efficient and effective way. Currently, the project design teams that have adopted building information modeling (BIM) are subject to constant changes in the techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…signifies “the extent to which a firm feels threatened by and tries to evade ambiguous situations in the supply chain” (Zhang & Cao, 2018, p. 149). It denotes how collaborative partners seek to eschew ambiguity and vagueness in their relationships with other supply chain members (Seo et al, 2016; Villena-Manzanares et al, 2020; Porcu et al, 2020; Le, 2021). Hence, Kumar and Rahman (2015) suggest that supply chain members faced with high levels of ambiguity and unpredictability turn to inter-organisational relationships for solace.…”
Section: Theoretical Background Concepts and Hypothesismentioning
confidence: 99%
“…signifies “the extent to which a firm feels threatened by and tries to evade ambiguous situations in the supply chain” (Zhang & Cao, 2018, p. 149). It denotes how collaborative partners seek to eschew ambiguity and vagueness in their relationships with other supply chain members (Seo et al, 2016; Villena-Manzanares et al, 2020; Porcu et al, 2020; Le, 2021). Hence, Kumar and Rahman (2015) suggest that supply chain members faced with high levels of ambiguity and unpredictability turn to inter-organisational relationships for solace.…”
Section: Theoretical Background Concepts and Hypothesismentioning
confidence: 99%
“…As a result, the team becomes much more united. Villena-Manzanares et al [40] showed the effectiveness of new technology-enhanced with senior management support. In order to achieve that, senior management support must encourage a collaborative culture and technical education among project team members.…”
Section: Company's Culturementioning
confidence: 99%
“…Once a new technology is accepted, it can only confer the desired effect with the support of the leaders. To do this, senior management support must facilitate collaboration and technological learning among organizational members [55].…”
Section: Impact Of Incentives On Organizational Culturementioning
confidence: 99%